Competition Enforcement and Accounting for Intangible Capital - KEPLER, JOHN D.; MCCLURE, CHARLES G.; STEWART, CHRISTOPHER R. (Journal of Finance, 2026)
ABSTRACT Antitrust laws mandate review of mergers and acquisitions (M&As) that exceed an asset size threshold based on accounting standards that exclude most intangible capital. We show that this exclusion leads to thousands of intangible‐intensive M&As being nonreportable. Acquirers in nonreportable deals achieve higher equity values and price markups, especially when consolidating product markets. Furthermore, nonreportable pharmaceutical deals are three times more likely to involve overlapping drug projects, which are subsequently 40% more likely to be terminated. Our results suggest that the growth of intangible assets may exacerbate market power through nonreportable consolidation of the sectors most concerning for consumers.